Reflections on territorial strategies for sustainable development (ECLAC SantiagoCL, 1998)
Presents proposals for improving environmental management at the territorial level, including practical suggestions for shaping strategies.
Prepared for the Summit Conference on Sustainable Development held at Santa Cruz, Bolivia 7 & 8 December 1996. Bibliography: p.15